Wallace Stevens The Making of the Poem - Doggett, Frank (Johns Hopkins University Press, 2020)
Originally published in 1980. Wallace Stevens: The Making of the Poem emphasizes the ideas that Wallace Stevens embeds in his poetry, providing the first study to provide an intellectual biography of Stevens. It examines Stevens' naturalism, his ideas of the self, and the imagination, among other topics. The concepts that emerge from long reading of the poetry of Stevens are slight and basic, but these concepts do accord, even if they never emerge into a coherent philosophy. The accordance is probably a result of Stevens' preference for naturalistic thought.